Korelasi Antara Reseptor Hormonal Dengan Grading Histologi Pada Karsinoma Payudara - Edy Supriyanto, - (2004)
Background: The administration of adjuvant therapy requires the identification of certain factors in order to predict therapeutic outcome and to determine the prognosis of patient's illness. According to St. Gallen's 2001 concensus, the administration of hormonal therapy is indicated in the presence of hormonal receptor within the tissue specimen. Estrogen receptors are mainly found in low-grade breast carcinoma. Until the present day, the standard test for breast carcinoma specimen is histopathologic examination, in which histologic grading can be performed. Objective : To evaluate the correlation between hormonal receptors and histologic grading in breast carcinoma Method : This is a cross-sectional research. Research samples amounted to 22 subjecs, obtained from operative specimens from patients with breast carcinoma, receiving treatment in the oncology division of the surgery department at Soetomo Hospital, Surabaya. Histopathologic and immunohistochemical examinations were performed on all samples. The statistical analysis test used was Spearman's correlation test. Result: In this research, 12 (54.5%) of the subjects were poorly differentiated, 8 (36.4%) were moderately differentiated and 2 (4.1 %) were well differentiated. Correlational analysis proved that there was a significant correlation between histologic grading and estrogen receptor with a correlation coefficient of -0.839 and p=O.OOO. Additionally, it also demonstrated a significant correlation between histologic grading and progesterone receptor with a correlation coefficient of -0.594 and p=O.004. Conclusion : The histologic grading of patients with breast carcinoma correlated with hormonal receptors, the higher the histologic grading the lower the hormonal receptors levels.